Blockchain-based IoT Systems: Techniques, Applications, and Challenges (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The potential for blockchain-based IoT systems to enable secure and effective data sharing in a variety of industries has attracted a lot of attention in recent years. The fusion of blockchain technology and IoT devices can open up new avenues for growth and innovation, but it also comes with a number of serious drawbacks, including issues with scalability, security, interoperability, data privacy, cost, energy use, and governance. This study offers a thorough analysis of the various methods for putting into practise Blockchain-based IoT systems, along with their benefits and drawbacks. In order to address the issues with Blockchain-based IoT systems, we also suggest a hybrid technique that combines the benefits of several techniques. We also cover the important issues that need to be solved as well as the potential uses of Blockchain-based IoT devices. In order to help researchers and practitioners better grasp the current state of the art and the possibilities for further study and development, this paper seeks to provide a thorough review of Blockchain-based IoT systems.